Overview of SAP System in Sarawak Energy Berhad/ Daisy James - James, Daisy (1986)
Sarawak Energy Berhad is a fully integrated electric utility responsible for the generation,transmission and distribution of electricity in the state of Sarawak. Sarawak, being the largest state in Malaysia, has over 20,000MW of identified hydro potential, ensuring plentiful and reliable energy for the future at very competitive prices. With solid financial credentials, Sarawak Energy looks set to fulfil the State's ambition to attract energy industries to Sarawak. Sarawak Energy is now being transformed into a major energy and utility player in Sarawak as well as in the region via the consolidation of the State power generation, transmission, the power and energy provider, spearheading the thrust as the State's flagship energy and utility group, hence complementing the rapid development growth of Sarawak.